Design and implementation of virtual laboratories for higher education sustainability: a case study of Nankai University - Zhang, Nan; Liu, Yin (Frontiers in Education, 2024)
Laboratory learning has a vital role in science education. With the application of information technologies in educational domain, virtual experiment has become an effective supplement to traditional experimental teaching. Moreover, virtual experimentation can expand experimental field, enrich teaching content and reduce experimental risk, which provides strong support for the sustainable development of higher education.Using cutting-edge technologies such as virtual reality (VR), augmented reality (AR), computer simulation and interaction, we developed two public virtual laboratories and 41 virtual-simulationexperiment projects. They are integrated into an interactive learning environment, that is, virtual experiment learning management platform. The method is based on ADDIE (Analysis, Design, Development, Implementation, and Evaluation).In this paper, one virtual-simulation-experiment project is taken as a case study. The project includes 4 virtual practical activities mapped to the medical courses; and they were implemented in the third year of the bachelor's degree. The proposed virtual learning environment has been evaluated by learners for two years. The results achieved and similar findings from other studies, show that the use of virtual learning environment has a positive impact on the learning process and outcomes.